MEDIA AGAMI UNTUK PEMBELAJARAN TEMATIK SISWA KELAS III SD - Remanda Wahyu Intisari; Marinda Sari Sofiyana; Mar’atus Sholihah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The problems obtained from the preliminary study indicated that there was no learning media for thematic learning for